Biologic Therapies in Chronic Rhinosinusitis with Nasal Polyposis: Current Evidence and Future Perspectives - Setiawan , Gunawan Wijaya (CoinReads Media Prima, 2025)
Chronic rhinosinusitis with nasal polyposis (CRSwNP) is a common type 2 inflammatory disease affecting approximately 1–4% of the population and is characterized by persistent nasal obstruction, olfactory dysfunction, facial pain, and substantial impairment in quality of life. Although standard therapies such as intranasal corticosteroids and endoscopic sinus surgery remain the mainstay of treatment, a significant proportion of patients experience recurrent or inadequately controlled disease. Improved understanding of the immunopathogenesis of CRSwNP has highlighted the central role of type 2 inflammation, driven by cytokines including interleukin-4, interleukin-5, interleukin-13, and immunoglobulin E, thereby enabling the development of targeted biologic therapies. Biologic agents such as dupilumab, mepolizumab, benralizumab, and omalizumab have demonstrated consistent efficacy in phase III randomized controlled trials and real-world studies, leading to significant reductions in nasal polyp burden, improvements in Sino-Nasal Outcome Test (SNOT-22) scores, restoration of olfactory function, and decreased need for systemic corticosteroids and revision surgery. Patient selection is increasingly guided by clinical phenotype and biomarkers, including blood eosinophil counts, total serum IgE levels, and the presence of comorbid asthma or aspirin-exacerbated respiratory disease. Emerging evidence supports the integration of biologic therapy with surgical management in refractory cases, while ongoing trials targeting upstream mediators such as interleukin-33 and thymic stromal lymphopoietin may further expand therapeutic options. Overall, biologic therapies represent a paradigm shift in the management of severe CRSwNP, paving the way toward precision-based, individualized treatment strategies.